Precise determination of polarization fields in c-plane GaN/AlxGa1-xN/GaN heterostructures with capacitance-voltage-measurements - Susilo, Norman; Schilling, Marcel; Narodovitch, Michael; Yao, Hsin-Hung; Li, Xiaohang; Witzigmann, Bernd; Enslin, Johannes; Guttmann, Martin; Roumeliotis, Georgios G.; Rychetsky, Monir; Koslow, Ingrid; Wernicke, Tim; et al. (Japanese Journal of Applied Physics, 2019)
Due to changes in the spontaneous and piezoelectric polarization, AlGaN/GaN heterostructures exhibit strong polarization fields at heterointerfaces. For quantum wells, the polarization fields lead to a strong band bending and a redshift of the emission wavelength, known as quantum-confined Stark effect. In this paper the polarization fields of thin AlGaN layers in a GaN matrix were determined by evaluating the changes in the depletion region width in comparison to a reference sample without heterostructure using capacitance-voltage-measurements. The polarization fields for Al0.09Ga0.91N (0.6 ±0.7 MV cm-1), Al0.26Ga0.74N (2.3 ±0.6 MV cm-1), Al0.34Ga0.66N (3.1 ±0.6 MV cm-1), Al0.41Ga0.59N (4.0 ±0.7 MV cm-1) and Al0.47Ga0.53N (5.0 ±0.8 MV cm-1) heterostructures were determined. The results of the field strength and field direction of all samples are in excellent agreement with values predicted by theory and a capacitance-voltage based Poisson-carrier transport simulation approach giving experimental evidence for a nonlinear increasing polarization field with Al-concentration.
CRIS-Team Scopus Importer:2021-06-11